THE TRUST AND DISTRUST OF INTELLECTUAL PROPERTY RIGHTS - Yu, Peter (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2005)
Access to information and knowledge is closely linked to intellectual property rights, and a fair, balanced, and robust international intellectual property regime is needed to give everybody an equal opportunity to fully participate in the information revolution. This article examines the international intellectual property regime as it relates to the development of an inclusive global information society. It begins by providing an overview of intellectual property rights and justifications for protecting those rights. It then explores the increased distrust of the intellectual property system, especially among less developed countries, human rights advocates, development specialists, and those on the unfortunate side of the digital divide. The article delineates five prerequisites for the development of a fair, balanced, and robust international intellectual property regime: (1) thorough understanding, (2) balanced debate, (3) equal dialogue, (4) a fair regime, and (5) global solidarity. It concludes by critically examining those portions of the WSIS Declaration of Principles and Plan of Action that are related to intellectual property and traditional knowledge.